Effects of High Ammonium Loading on Two Submersed Macrophytes of Different Growth Form Based on an 18-Month Pond Experiment - Yu, Qing; Wang, Haijun; Wang, Hongzhu; Xu, Chao; Liu, Miao; Ma, Yu; Li, Yan; Ma, Shuonan; Hamilton, David P.; Jeppesen, Erik (Frontiers in Plant Science, 2022)
Ammonium (NH4-N) produces a paradoxical effect on submersed macrophytes because it is the preferred nitrogen source for the growth of plants, but also threatens the growth of plants at high concentration. Whether the short-term and small-scale physiological toxicity experiments at individual level can reflect the effects of high ammonium on the populations of submersed macrophyte in natural conditions is still unclear. In this study, an 18-month experiment was conducted in six 600 m2 ponds subjected to different levels of ammonium loading. The effects of high ammonium on populations of canopy-forming Myriophyllum spicatum and rosette-forming Vallisneria natans were explored. The results showed that M. spicatum and V. natans populations can develop high cover and height at high ammonium concentration (7 mg L-1), and V. natans may be tolerant to 18 mg L-1 ammonium concentration. The rosette-forming V. natans resists ammonium stress by slow growth (shoot elongation) to reduce consumption, while canopy-forming species resists ammonium stress by shoot elongation and canopy development to capture light. Though increasing ammonium concentration may induce severe stress on M. spicatum, the physiological and morphological characteristics of this species may to some extent release the plants from this stress. Our present study indicates that the populations of both growth forms can disperse at high NH4-N concentration in most natural aquatic ecosystems, and the stress effect of NH4-N is weak when extrapolating to natural systems. However, in strongly ammonium-enriched systems, competition, succession, and exposure duration cannot be neglected.